Synthesis and properties of bis((4-R-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazol-3-yl)thio)alkanes - O. A. Suhak; O. I. Panasenko; Ye. H. Knysh (Zaporozhye State Medical University, 2018)
The aim of this work was the synthesis of bis((4-R-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazol-3-yl)thio)alkanes using available reagents and study of their properties. Matherial and methods. 4-R-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazol-3-thiol was used as an intermediate compound, obtained from methyl 2-(thiophen-2-yl)acetate. Its synthesis has been described in previous studies. During the bis((4-R-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazol-3-yl)thio)alkane moiety formation stage, dibromoalkanes (dibromomethane, dibromopropane, dibromobuthane) were used as secondary reagents. The reaction was conducted in propan-2-ol. The presence of reaction products has been confirmed applying spectral methods. Synthesis of bis((4-R-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazol-3-yl)thio)alkanes 0.01 M of the correspondent alkyl halide is added to the corresponding 3-(3-R-1,2,4-triazol-5-thiomethyl)-1,2,4-triazol-5-thione (0.01 M) in mixture of 0.01 mole NaОН and 30 mL of ethanol or propan-1-ol, and the mixture is boiled until the neutralization (during 3 hours reflux). The mixture is filtered, solvent is evaporated. White crystalline matter, practically insoluble in water, soluble in organic solvents. Compounds were purified by recrystallization from dimethylformamide-water mixture (1:1). Results. Distinction of compounds was confirmed by chromatography-mass-spectrometry. 1H NMR spectra of the obtained compounds were characterized by number of signals. The protons of alkylsulfide fragment resonate in a weak field appearing as multiplets at 3.12-3.07 ppm and 2.25-2.10 ppm. The protons of methyl group, which bond the heteroaromatic fragments together, resonate as a singlet at 3.92-3.87 ppm. Aromatic protons of thiophene fragments appear as multiplets at 6.95-6.78 and 6.99-7.20 ppm. The protons of methyl fragment of N-alkyl substituent appear as a multiplet at 4.21-3.98 ppm, protons of methyl fragment resonate as a triplet at 1.52-1.57 ppm. IR spectra of the studied compounds showed presence of C-S fragment, which appears as a band of molecular stretching at 693 cm-1. Stretching vibrations of С-H fragment of thiophene ring is observed at 715-693 cm-1. The CH2 fragment appears as strong stretching (at 2935-2905 cm-1 and 2865-2855 cm-1) and moderate bending vibrations (at 1493-1460 cm-1). Also recommended for "polymethylene fragment" are characteristic deformation vibrations at 730-720 cm-1. Symmetrical and asymmetrical bending at 1385-1380 and 1470-1465 cm-1characterize the presence of СН3 group. Preliminary screening of acute toxicity and biological activity parameters has been carried out. Conclusions. Nine compounds were obtained; their structures were confirmed.The characteristics of the synthesized compounds were assessed with computer processing using PASS online tool. The most promising compounds were selected for in vitro research. It was clarified during the analysis of results that the obtained compounds may exhibit various types of biological activities. The most probable effect predicted for the nine studied compounds is antimicrobial activity. 1,2,4-triazole, bis-derivatives, synthesis, IR spectroscopy, 1Н NMR spectroscopy, PASS-screening